Avaliação da concentração de radônio-222 no ar de postos de trabalho de Curitiba/PR - Del Claro, Flávia (2013)
In every day life people are exposed to various types of radiation arising from different artificial and natural sources and among all of them the main role belongs to the isotope of noble gas 222Rn that makes part of the 238U radioactive chain. The isotope 222Rn is responsible for approximately half of the effective annual dose received by the world population. Being inhaled, the radon isotopes have to undergo 8 radioactive decay events (one half by emitting alpha particles and another half by emitting betas) to get to a stable isotope of lead. This radiation interacting with the cells of biological tissue have very high probability to induce the lung cancer. The goal of present research is to evaluate the activity concentration of 222Rn in the air of workplaces at Curitiba – Paraná State. Simultaneously there were performed the measurements of 222Rn emanation from soil and building materials occurred at evaluated workplaces. Indoor measurements of 222Rn activity were performed using Polycarbonate track etched detectors CR-39 that after the exposition in air were submitted to chemical etching and manual reading using the optical microscope.The calculations of the activity concentration of 222Rn in the air of workplaces were completed using the results of calibration performed by the Center of Nuclear Technology Development (CDTN) in cooperation with the Laboratory of Applied Nuclear Physics of the Federal University of Technology - Paraná (UTFPR).The instant radon detector AlphaGUARD (Saphymo GmbH) was used in the measurements of the average concentrations of 222Rn in soil gas and building materials. Building materials were also submitted to gamma spectrometry analysis for qualitative and quantitative evaluation of the radionuclides present in samples of sand, mortar, blue crushed stone, red crushed stone, concrete and red bricks. The method used for the measurements of radon activity in soil gas allowed to find the average concentrations of two isotopes 222Rn and 220Rn. The average concentration of indoor 222Rn obtained in the measurements in air of workplaces vary between 36 ± 49 Bq/m³ and 164 ± 51 Bq/m³. These values are considered within the reference limit of 200 Bq/m³ established by international agencies such as the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) and the International Commission on Radiological Protection (ICRP), but slightly above the limit of 148 Bq/m³ established by the United States Environmental Protection Agency (USEPA). The measurements involving building materials presented the concentration values of 222Rn in a range from 427 ± 310 Bq/m³ to 2053 ± 700 Bq/m³. The 222Rn concentrations in soil ranged from 31 ± 2 kBq/m³ to 35 ± 4 kBq/m³ and the average values of 220Rn are found in a range of 41 ± 6 kBq/m³ and 25 ± 11 kBq/m³, thus the concentrations of radon gas soil are below the Swedish criterion of 50 kBq/m³ that represent the minimum value for high-risk situation.